A letra escarlate como romance histórico: uma história de fragilidade humana e tristeza - Oliveira, Albéris Eron Flávio de (2013)
The objective of this paper is to analyze the work of the American writer Nathaniel Hawthorne (1804 - 1864), The Scarlet Letter (1850), in the light of the contributions of Literature and History of the American people in the context of New England. Accordingly, we highlight aspects that justify the inclusion of the work as a historical novel, especially based on the reading of The Historical Novel (1936-37) written by Georg Lukács. The diversity of voices and social interrelationships that come out of the main characters of the plot of the novel, as well as their contextual buildings, constituted as important traces to understanding the novel as being of historical value. During our study, we found out that it is in the plots of the novels that the characters reflect, at the same time, the specific conditions of their singularities, the general trends of the historical process and the social conditions from which they arise. We also could see that it is in their singularities that lie special tendencies of human beings. Our references to this study came from scholars as Howard (1964), Bakhtin (1998), Eagleton (2006), Todorov (2009), Zabel (1947), Sellers (1985), Cunlife (1986), Candido (1993) and Schwarz (1981)